Elevated atmospheric CO2 levels affect community structure of rice root-associated bacteria - Okubo, Takashi; Liu, Dongyan; Tsurumaru, Hirohito; Ikeda, Seishi; Asakawa, Susumu; Tokida, Takeshi; Tago, Kanako; Hayatsu, Masahito; Aoki, Naohiro; Ishimaru, Ken; Ujiie, Kazuhiro; Usui, Yasuhiro; et al. (Frontiers in Microbiology, 2015)
A number of studies have shown that elevated atmospheric CO2 ([CO2]) affects rice yields and grain quality. However, the responses of root-associated bacteria to [CO2] elevation have not been characterized in a large-scale field study. We conducted a free-air CO2 enrichment (FACE) experiment (ambient + 200 μmol⋅mol−1) using three rice cultivars (Akita 63, Takanari, and Koshihikari) and two experimental lines of Koshihikari (chromosome segment substitution and near-isogenic lines) to determine the effects of [CO2] elevation on the community structure of rice root-associated bacteria. Microbial DNA was extracted from rice roots at the panicle formation stage and analyzed by pyrosequencing the bacterial 16S rRNA gene to characterize the members of the bacterial community. Principal coordinate analysis of a weighted UniFrac distance matrix revealed that the community structure was clearly affected by elevated [CO2]. The predominant community members at class level were Alpha-, Beta-, and Gamma-proteobacteria in the control (ambient) and FACE plots. The relative abundance of Methylocystaceae, the major methane-oxidizing bacteria in rice roots, tended to decrease with increasing [CO2] levels. Quantitative PCR revealed a decreased copy number of the methane monooxygenase (pmoA) gene and increased methyl coenzyme M reductase (mcrA) in elevated [CO2]. These results suggest elevated [CO2] suppresses methane oxidation and promotes methanogenesis in rice roots; this process affects the carbon cycle in rice paddy fields.